Individual adaptability and philanthropic behavior of Malaysian community health workers: social network as mediator - Alias, Siti Noormi; Ismail, Maimunah; Suandi, Turiman; Omar, Zoharah (2015)
Purpose - The study explored how individual adaptability factors impact philanthropic behavior among community health workers (CHWs), with social network as the mediator. Design/methodology/approach – this study used a correlational research design involving 230 CHWs under MERCY Malaysia, a non-government organization (NGO) in the health sector. The data were analyzed using a two-step approach in structural equation modeling (SEM), combining a measurement model and a structural model. Findings – Results showed that (1) social network fully mediated the relationship between task-oriented coping and philanthropic behavior and (2) social network partially mediated the relationship between social trust and philanthropic behavior. Research limitations/implications – The data of the study were generated from a single NGO (MERCY Malaysia) and considered only social adaptability as the antecedent. Originality/ value – The study is the first of its kind conducted in Malaysia. The finding that social network played a significant role as mediator in philanthropic behavior should be capitalized on by HRD practitioners to bridge the gap between theory and practice in the philanthropic work of CHWs.